Law Activation Strategies (LAS) in Environmental Policymaking: a Social Mechanism for Re‐politicization?. (September 2015) - Schweizer, Rémi
Abstract : Despite the exponential development of environmental policies, environmental problems persist and are constantly evolving. There is, clearly, a distance between the abstraction of rules and the concreteness of action. Going beyond the de‐politicization and institutional determinism that environmental policy analysis often conveys, this article suggests that the analysis should be re‐politicized in order to understand these gaps. Based on this reasoning, the concept of "law activation strategy" (LAS) is proposed as a social mechanism to analyze the complex interplay between legal rules, actors' behaviors, and environmental outcomes. Embedded within political games and asymmetric power relations, LAS cover the various positions that actors may take with regards to the rules that structure their action: concretization, passivity, diversion, circumvention, and innovation. The concept is integrated to a broader analytical framework and applied to an empirical case study related to aquatic ecosystem protection in Switzerland. By doing so, the paper demonstrates the explanatory power of LAS and its pertinence in providing a more political understanding of environmental policymaking.